'Feeling the rhythm of the waves: "castaway rhetoric" in John Eugenikos' Logos eucharisterios' *. (August 2013) - Pizzone, Aglae
Abstract : In September 1438 John Eugenikos decided to quit the council of Ferrara and sail back to Constantinople. Off Italy's Adriatic coast his vessel experienced a terrible shipwreck, whereby many of John's fellow-passengers perished. John decided then to retell his almost deadly experience in a thanks-giving logos, allegedly compiled on the basis of notes written down soon after the shipwreck. The logos stands out as a unique document in the landscape of Byzantine travel literature. This paper offers the first comprehensive literary analysis of Eugenikos' account, shedding new light on the narrative patterns chosen by the author to recount his own experience and stage his public persona.